Changes in sociodemographic characteristics at baseline in two Swedish cohorts of patients with early rheumatoid arthritis diagnosed 1996–98 and 2006–09. (March 2015) - Hallert, E; Husberg, M; Kalkan, A; Rahmqvist, M; Skogh, T; Bernfort, L
Abstract : Objectives: To compare baseline sociodemographic characteristics in two rheumatoid arthritis (RA) cohorts enrolled 10 years apart, and to examine differences with respect to the general population. Method: Clinical and sociodemographic data were collected in 320 early RA patients during 1996–98 (TIRA-1) and 467 patients in 2006–09 (TIRA-2). Multivariate logistic regression tests were performed and intercohort comparisons were related to general population data, obtained from official databases. Results: TIRA-2 patients were older than TIRA-1 (58 vs. 56 years). Women (both cohorts, 67%) were younger than men in TIRA-1 (55 vs. 59 years) and in TIRA-2 (57 vs. 61 years). Disease activity was similar but TIRA-2 women scored worse pain and worse on the HAQ. Approximately 73% were cohabiting, in both cohorts and in the general population. Education was higher in TIRA-2 than in TIRA-2 but still lower than in the general population. Women had consistently higher education than men. Education was associated with age, younger patients having higher education. In both cohorts, lower education was associated with increased disability pension and increased sick leave. Sick leave was lower in TIRA-2 than in TIRA-1 (37% vs. 50%) but disability pension was higher (16% vs. 10%). In TIRA-1, 9% of women had disability pension compared with 17% in TIRA-2. A similar decrease in sick leave and an increase in disability pension were also seen in the general population. Older age and a higher HAQ score were associated with increased sick leave and being in the TIRA-2 cohort was associated with decreased sick leave. Conclusions: TIRA-2 patients were slightly older, better educated, had lower sick leave and higher disability pension than those in TIRA-1. Similar changes were seen simultaneously in the general population. Belonging to the TIRA-2 cohort was associated with decreased sick leave, indicating that societal changes are of importance.